2008
DOI: 10.1177/0886260508322184
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Witnessing Community Violence and Direct Victimization Among Children in Cape Town, South Africa

Abstract: This study is based on a sample of children from the Cape Town area in South Africa. The study compares the effects of witnessing school or neighborhood violence compared with being victimized in each context on psychological distress. The findings suggest that in the context of the school, victimization has a somewhat stronger effect on distress than witnessing violence. However, in the neighborhood, the opposite was the case. "Unknown locus of control" was also analyzed as a moderating variable. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 21 publications
5
49
0
1
Order By: Relevance
“…Although direct comparison between our community sample and the national probability sample used by Zinzow et al (2009) is methodologically limited, it is possible that the much higher levels of witnessing violence reported in our sample may contribute to a desensitization effect for witnessed violence. However, in a previous South African study with a younger and more culturally diverse sample, Shields et al (2009) reported that both witnessed and direct victimization contributed independently to posttraumatic stress symptoms. It is therefore possible that the desensitization effect for witnessing violence may be more specific to Xhosa adolescents due to particular contextual or cultural factors.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Although direct comparison between our community sample and the national probability sample used by Zinzow et al (2009) is methodologically limited, it is possible that the much higher levels of witnessing violence reported in our sample may contribute to a desensitization effect for witnessed violence. However, in a previous South African study with a younger and more culturally diverse sample, Shields et al (2009) reported that both witnessed and direct victimization contributed independently to posttraumatic stress symptoms. It is therefore possible that the desensitization effect for witnessing violence may be more specific to Xhosa adolescents due to particular contextual or cultural factors.…”
Section: Discussionmentioning
confidence: 80%
“…While it is apparent that cumulative trauma exposure as well as specific forms of violence are associated with a range of internalizing and externalizing symptomatology among South African youth (Seedat, Nyamai, Njenga, Vythilingum, & Stein, 2004;Shields, Nadasen, & Pierce, 2008Suliman et al, 2009;Ward, Martin, Theron, & Distiller, 2007), the comparative contributions of particular forms of violence are less clear. One previous study reported that both community violence and childhood abuse contributed independently to PTSD symptoms in South African adolescents (Fincham, Korthals Altes, Stein, & Seedat, 2009), while another found that both witnessing and direct victimization in the community contributed independently to psychological distress (Shields et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence comes from both cross-sectional and prospective studies demonstrating a dose-response relationship between bullying victimization and mental health in different samples and using differing measures (Arseneault et al 2010;Fekkes et al 2006). More specifically, two cross-sectional South African studies have demonstrated relationships between bullying victimization, symptoms of anxiety, and depressive symptoms in community samples of children and adolescents (Cluver et al 2010;Shields et al 2009) and a recent prospective South African study has demonstrated that bullying victimization is predictive of internalising symptoms (including anxiety symptoms and depressive symptoms) measured one year later, even after adjusting for poverty (Boyes et al 2014). Furthermore, in a large sample of South African children and adolescents, Cluver et al (2010) reported that caregiver HIV/AIDS-sickness and HIV/AIDS-related stigma are risk factors for bullying victimization.…”
Section: Bullying Victimization and Mental Healthmentioning
confidence: 99%
“…Selon certains auteurs, la violence communautaire réfère à la violence vécue en tant que victime ou témoin, près de la maison, de l'école et à l'intérieur du voisinage (Scarpa, 2003 ;Shields et al, 2009). Certaines études éta-blissent des distinctions selon que l'incident implique ou non une arme, une agression physique, ou selon l'endroit où l'acte violent est commis (Stein et al, 2003 ;Barroso et al, 2008).…”
Section: Définition De La Violence Communautaireunclassified